Institutions, Equilibria and Efficiency Essays in Honor of Birgit Grodal - Schultz, Christian; Vind, Karl.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2006)
Competition and efficiency is at the core of economic theory. This volume collects papers of leading scholars, which extend the conventional general equilibrium model in important ways: Efficiency and price regulation are studied when markets are incomplete and existence of equilibria in such settings is proven under very general preference assumptions. The model is extended to include geographical location choice, a commodity space incorporating manufacturing imprecision and preferences for club-membership, schools and firms. Inefficiencies arising from household externalities or group membership are evaluated. Core equivalence is shown for bargaining economies. The theory of risk aversion is extended and the relation between risk taking and wealth is experimentally investigated. Other topics include determinacy in OLG with cash-in-advance constraints, income distribution and democracy in OLG, learning in OLG and in games, optimal pricing of derivative securities, the impact of heterogeneity at the individual level for aggregate consumption, and adaptive contracting in view of uncertainty.
Birgit Grodal: A Friend to Her Friends -- On the Definition of Differentiated Products in the Real World -- Equilibrium Pricing of Derivative Securities in Dynamically Incomplete Markets -- Adaptive Contracting: The Trial-and-Error Approach to Outsourcing -- Monetary Equilibria over an Infinite Horizon -- Do the Wealthy Risk More Money? An Experimental Comparison -- Are Incomplete Markets Able to Achieve Minimal Efficiency? -- A Competitive Model of Economic Geography -- The Organization of Production, Consumption and Learning -- Household Inefficiency and Equilibrium Efficiency -- Equilibrium with Arbitrary Market Structure -- Pareto Improving Price Regulation when the Asset Market is Incomplete -- On Behavioral Heterogeneity -- Learning of Steady States in Nonlinear Models when Shocks Follow a Markov Chain -- The Evolution of Conventions under Incomplete Information -- Group Formation with Heterogeneous Feasible Sets -- Monotone Risk Aversion -- Will Democracy Engender Equality? -- Consumption Externalities, Rental Markets and Purchase Clubs -- Core-Equivalence for the Nash Bargaining Solution.
Keywords: Economic theory; Econometrics; Economics; Economic Theory/Quantitative Economics/Mathematical Methods; Econometrics; Electronic books